An early bone tool industry from the Middle Stone Age at Blombos Cave, South Africa: implications for the origins of modern human behaviour, symbolism and language - (:unkn) unknown (My University, 2001)
Twenty-eight bone tools were recovered in situ from ca. 70 ka year old Middle Stone Age levels at Blombos Cave between 1992 and 2000. These tools are securely provenienced and are the largest collection to come from a single African Middle Stone Age site. Detailed analyses show that tool production methods follow a sequence of deliberate technical choices starting with blank production, the use of various shaping methods and the final finishing of the artefact to produce ‘‘awls'' and ‘‘projectile points''. Tool production processes in the Middle Stone Age at Blombos Cave conform to generally accepted descriptions of ‘‘formal'' techniques of bone tool manufacture. Comparisons with similar bone tools from the Later Stone Age at Blombos Cave, other Cape sites and ethnographic collections show that although shaping methods are different, the planning and execution of bone tool manufacture in the Middle Stone Age is consistent with that in the late Holocene. The bone tool collection from Blombos Cave is remarkable because bone tools are rarely found in African Middle or Later Stone Age sites before ca. 25 ka. Scarcity of early bone tools is cited as one strand of evidence supporting models for nonmodern behaviour linked to a lack of modern technological or cognitive capacity before ca. 50 ka. Bone artefacts are a regular feature in European sites after ca. 40 ka, are closely associated with the arrival of anatomically modern humans and are a key behavioural marker of the Upper Palaeolithic ‘‘symbolic explosion'' linked to the evolution of modern behaviour. Taken together with recent finds from Klasies River, Katanda and other African Middle Stone Age sites the Blombos Cave evidence for formal bone working, deliberate engraving on ochre, production of finely made bifacial points and sophisticated subsistence strategies is turning the tide in favour of models positing behavioural modernity in Africa at a time far earlier than previously accept
Keywords: African Research